Diet and foraging areas of Southern Ocean seabirds and their prey inferred from stable isotopes: review and case study of Wilson’s storm-petrel - Quillfeldt, Petra; McGill, Rona A.R.; Furness, Robert W. (2021)
Analysis of stable isotope ratios in animal tissues has emerged as a powerful tool for determining the trophic level and composition of prey and foraging location. We summarize here data on the stepwise trophic enrichment in δ15N and latitudinal gradient in δ13C in the Southern Ocean, and derive a regression equation to estimate latitudes from δ13C values. We analysed isotope ratios of feathers of the small, pelagic seabird Wilson’s storm-petrel Oceanites oceanicus, in different breeding stages, in comparison to isotope ratios of 4 other seabird species breeding in close vicinity on King George Island, South Shetland Islands. δ15N analysis of feathers and albumen from Wilson’s storm-petrels indicated a shift in diet from mainly crustaceans during egg formation to an increased proportion of fish during chick-feeding and moulting. δ15N values of Wilson’s storm-petrels during the chick-rearing season were closer to the mainly piscivorous-carnivorous skuas than to krill-feeding penguins, confirming that fish is an important part of their diet. δ13C analysis of feathers identified 4 distinct foraging areas: δ13C values in egg-white suggest that egg-forming females moved south to the sea ice edge. This coincides with the distribution of their main prey, Antarctic krill Euphausia superba, during this period. During the breeding season, Wilson’s storm-petrels fed in the area around the colony, which is also used by penguins and skuas. δ13C of the feathers indicate that adults migrated to the Subtropical Front and beyond (north of 44°S) during the inter-breeding period. Feathers were also analysed from 10 Wilson’s storm-petrels caught by mistnet and thought to be prebreeders because they lacked foot markings; 8 of these had moulted in the same area as breeding birds, while 2 birds had moulted in an area further north (north of 30°S). Adélie penguins Pygoscelis adeliae and Gentoo penguins P. papua had significantly different δ13C, suggesting that the Adélie penguins foraged further south than the Gentoo penguins. The ...